Student Achievement Based on the Use of Scientific Method in the Natural Science Subject in Elementary School (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
This research aims at investigating elementary school student achievement based on the use ofscientific method in teaching science from the test item types, as reflected by the item difficulty indexusing the classical test theory (CTT) and modern test theory (IRT). The first stage in developing the test was preparing the learning continuum of scientific method aspects by referring to the learning continuum of science process skill as developed by the previous existing research. In this research, the learning continuum was validated by expert judgment. As the tests were administered/carried out at the same time, four sets of tests were developed and administered to students of Grade 1 to 6 in Yogyakarta and Sleman Regency in the 2016-2017 school year. Samples were taken from three Technical Management Units (TMUs). Three TMUs were determined by observing the distribution of school locations from the center to the suburbs. The items were analyzed using CTT and IRT.The results of the research show that the student achievement reflected by item difficulty index based on CTT and IRT indicates the same level of category except for several sub-aspects. Those items from certain testsindicate higher difficulty level for Grade 4 to 6 students than for Grade 1 to 3 students. This case is not relevant to the expected learning outcomes.